Frequency of metastasis to posterior triangle and lower deep jugular lymph nodes in patients with squamous cell carcinoma of oral cavity having clinically N1 neck - Varchasvi, Shilpa; Moyihuddin, Azeem (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Oral cancer is the sixth most common cancer in the world and is largely preventable. The objective of the study is to find out the frequency of metastasis to posterior triangle lymph nodes and lower deep jugular (supraclavicular) lymph nodes in patients with squamous cell carcinoma of oral cavity having clinically N1 neck. Methods: A hospital based prospective study. This prospective study was conducted in R. L. Jalappa Hospital and Research Centre and SDU Medical College Kolar, Karnataka. 30 patients having oral squamous cell carcinoma with clinically N1 neck (single ipsilateral lymph node less than 3cms in diameter) undergoing modified radical neck dissection in R. L. Jalappa Hospital and Research Centre. Results: In our study, 4 were male (13%) and 26 were females (87%). The age of the patients ranged from 41-70 years with a mean age of 53 years. Majority of primary tumours were buccal mucosa tumours (24). We had 6 anterior 2/3rd tongue tumours. The primary tumour staging included 17 T2 lesions (57%), 3 T3 lesions (10%), 10 T4 lesions (33%) in patients with buccal mucosa carcinoma, fourteen patients had T2 disease, 9 patients had T4 and one patient had T3 disease. Conclusions: Most common nodal involvement in buccal mucosa carcinoma was level Ib (submandibular lymph node). The incidence of level IV (supraclavicular) and level V (posterior triangle) lymph node metastasis is low in buccal mucosa carcinoma patients with clinically N1 neck.